Geopyxis carolinae sp. nov. (Pezizomycetes, Ascomycota) from Mexico - Sánchez-Flores, Marcos; García-Jiménez, Jesús; Martínez-González, César R.; Ekanayaka, Anusha H.; Raymundo, Tania (Phytotaxa, 2024)
Geopyxis is an ectomycorrhizal genus found in temperate forests. The members form yellow and orange to brown apothecia that range from 3–25 mm in diameter. Its ascospores are smooth to finely verrucous. The specimen collected from Mount Tlaloc, Texcoco, State of Mexico, was identified as Geopyxis carolinae sp. nov. This species typically forms sessile apothecia, cupuliform to discoid, and its ascospores are the largest [17–23(25) × 10–12 µm] within the genus. The species was found growing on a burnt ground associated with Abies religiosa. Multi-gene phylogenetic analyses inferred from ITS and LSU sequence data confirmed that Geopyxis carolinae is distinct from other Geopyxis spp. The new species is described, illustrated, and compared with similar taxa based on molecular and morphological data.